Puritans on prayer - Preston, John, 1587-1628; Vincent, Nathaniel, 1644?-1697; Lee, Samuel, 1627-1691?; Kistler, Don (Morgan, PA Soli Deo Gloria, 1995)
Contents : The saint's daily exercise / John Preston ; The spirit of prayer / Nathaniel Vincent ; Secret prayer / Samuel Lee.
Keywords: Prayer -- religious aspects -- Christianity -- historical writings